Exploring adolescents’ indirect financial and non-financial barriers to dental care non-attendance: the role of payment methods - Alla T. Alsharif; Saba Kassim (Frontiers in Public Health, 2025)
Background and aimsDental attendance is key to the prevention and early detection of oral diseases. In Saudi Arabia (SA), dental care is publicly funded for citizens; however, many families opt for private care through insurance or out-of-pocket payment. This study has twofold: (1) to examine factors associated with regular dental attendance versus non-dental attendance among adolescents, and (2) to explore the indirect financial and non-financial barriers to dental non-attendance, with a particular emphasis on how payment methods influence these barriers.MethodsAn analytical cross-sectional survey was conducted among a convenience sample of adolescents in Al-Madinah, SA. Data collected included socio-demographic characteristics, oral health related variables (e.g., brushing teeth, dental attendance pattern) and barriers to non-dental attendance. Logistic regression identified factors associated with non-attendance for dental care. To analyse non-dental attendance drivers, we organised response into six thematic domains: affordability, availability, accessibility, motivation, perceived need, and fear/anxiety. We then classified affordability—including transportation costs, productivity loss, and childcare expenses—as an indirect financial barrier, whereas the remaining domains (availability, accessibility, motivation, perceived need, and fear/anxiety) were defined as non-financial barriers. These were compared in relation to the participants’ payment methods.ResultsAmong 416 adolescents, (203 males, 48.9%), 315 (75.7%) reported non-dental attendance and 216 (51.9%) used out-of-pocket payment. Regression analysis showed that being male, using publicly funded dental services, and self-rating poor oral health were significantly associated with non-dental attendance (AOR = 2.42; 95% CI: 1.39–4.20; p = 0.002; AOR = 2.00; 95% CI: 1.07–3.75; p = 0.030; AOR = 2.32; 95% CI: 1.05–5.10; p = 0.037, respectively). Indirect financial barriers—such as parental childcare responsibilities and travel costs—were comparable across all payment methods. Fear and anxiety (as non-financial barriers) were more prevalent among adolescents using out-of-pocket or insurance payment methods (p = 0.021).ConclusionA high rate of adolescents dental non-attendance was significantly associated with demographic, economic factors, as well as with perceived oral health. Both indirect financial and non-financial barriers—except fear and anxiety—were frequently reported among adolescents regardless of payment method. This suggests the need for cost-efficient strategies (e.g., transport support), and psychoeducational approaches to improve dental attendance for both adolescents and their families.